2022
DOI: 10.1007/s00404-022-06818-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of the fetal brain biometry: an MRI-based study

Abstract: Purpose: Fetal growth assessment is a key component of prenatal care. Sex-speci c fetal brain nomograms on ultrasound are available and are clinically used. In recent years, the use of fetal MRI has been increasing, however, there are no sex-speci c fetal CNS nomograms on MRI. Study aims were to asses the differences in fetal brain biometry and growth trajectories, and to create population-based standarts of the fetal brain on MRI.Methods: In this cross-sectional study, brain structures of singelton fetuses wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Interpretation of missing values in US images must consider that non-pathological screening brain ultrasounds may lack targeted CC images. Gender impact was not assessed, as sexual dimorphism’s effect on fetal CC remains uncertain, with studies showing both influence ( 28 ) and lack thereof ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation of missing values in US images must consider that non-pathological screening brain ultrasounds may lack targeted CC images. Gender impact was not assessed, as sexual dimorphism’s effect on fetal CC remains uncertain, with studies showing both influence ( 28 ) and lack thereof ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous work by Gafner et al, which showed that there is no statistically significant difference in the TCD and in the length of CC between the different sexes [19], we performed the analysis on all cases without dividing into groups based on fetal sex.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ratio of missing values in US images must be interpreted with caution as patients with a screening brain ultrasound that was not pathological do not necessarily have targeted CC images. Finally, gender effect was not evaluated but sexual dimorphism on fetal CC is still unclear, with studies that did (24) and did not show impact of gender (46).…”
Section: Limitationsmentioning
confidence: 99%